Инциденција и преваленција на тироиден карцином во Република Македонија (1999-2010) - Makazlieva, Tanja; Vaskova, Olivija; Tripunoski, Toni; Majstorov, Venjamin (My University, 2017)
Epidemiological data indicates that thyroid carcinoma (TC) is the most frequent endocrinological tumors, participating with around 1% from all malignomas. Because of lack of published papers related to the epidemiological data for TC in the last two decades in our country especially after the introduction of corrected Iodine prophylaxis program, with new higher Iodine supplementation in 1999, there is a need for publishing real scientific view of the epidemiological situations. The aim of the study was to present epidemiological data on incidence and prevalence rate of TC in R Macedonia for the period 1999-2010. Materials and methods: A retrospective analysis of medical data from all diagnosed and treated TC at the Institute of Pathophysiology and Nuclear Medicine during the period 1999-2010 was performed. The Institute is the only Center performing treatment of TC with 131I, therefore the registered epidemiological data are representative for the country. Statistical State Office data from the census in 1994 and 2002 were used to calculate annual incidence and prevalence rate as well as geographical and ethnic country distribution of TC. Results: During 12-year period, a total of 204 TC cases were registered, with prevalence rate of 10.15/105. The highest incidence rate was detected in 2000 (1.18/105) followed by reduction in 2003 (0,49/105). Annual incidence rate showed continuously higher incidence rate in the period 2006-2010 with average incidence rate of 0.98/105. Results indicate quite similar incidence rate among the three ethnic groups while the regional distribution indicates the highest prevalence in Skopje region, East and Northeast region than Southwest region. The lowest prevalence rate was registered in Polog, Southeast and Pelagonia region. Conclusions: According to the analyzed data from the diagnosed patients with TC during the period 1999 – 2010, there is increase in the incidence and prevalence rate, but however compared with the literature is still very low. Major differences in morbidity rate concerning the ethnic distribution were not found. Related to the geographical distribution of TC in eight regions, the highest prevalence rate was found in northern and eastern parts, while the lowest in western territories. Further analyzes are needed to compare it with the previous epidemiological data in the country, as well as an analysis for possible environmental effects for the low incidence rate, compared to those from literature.
Incidence and prevalence of thyroid carcinoma in Republic of Macedonia (1999-2010)
Keywords: thyroid carcinoma; epidemiology; incidence rate; prevalence rate; mortality